The New 18: Research on Ideal Age for Employment in Mainstream Jobs - Kodi, Archana (Digital Repository of Theses, 2025)
Today’s teenagers are hungrier for independence and purpose orientation. Our employment models need to adapt rapidly to leverage these multitalented individuals at a rate of knots. The main research question being addressed here is whether being 18 or at age of majority should be linked in future to mainstream careers. The New 18 is a quest exploring the readiness and desire of today's teenagers, referred to as “The Aspirants,” to start working earlier in mainstream jobs or business ventures. A primary research was conducted with 250 respondents, aged 13-18, with a focus on their readiness and desire for earlier employment and factors influencing their stress levels, attitudes, emotions, and aspirations in the transit period of completing education to starting employment/entrepreneurship. This transit period is defined as the "Tedium Period," – the time between The Aspirant’s readiness to contribute and when they get the opportunity to do so. We observe the higher achievers experiencing a stronger desire to contribute sooner than 18. This period can be wearisome for The Aspirants influenced by factors such as economic status, skill readiness, and desire to contribute. Key findings of research emphasize the need to reevaluate age of mainstream employment for Gen-Z and Gen Alpha. An average of 70% respondents express the desire to start working in part-time/full-time jobs earlier than 18. The biggest drive to do so is financial independence followed by desire to progress sooner in career or add value to a higher purpose. We observe academic performance of students scoring >70%, age group of 16-19, and respondents from lower-income families appear more likely to feel confident about starting work or a business early, challenging the traditional view that only graduates are ready for mainstream jobs. Overall, the study concludes that most respondents agree with the need for "The New 18," a new age for teenagers who are skilled and advanced to jumpstart. It also highlights the role of educationalists, employment influencers, and government authorities in leveraging this untapped potential to contribute to mainstream job roles and innovative business ventures. The study calls for a change in traditional educational models to accommodate this shift.